A ESTRUTURA DO ENSINO SUPERIOR NO BRASIL - Leonardo Roth (Universidade Federal de Santa Catarina, 2013)
Higher education in Brazil has recently undergone a makeover legal and structural. In a context where the country stands on the world stage as a developing market that is beginning to attract the attention of large multinational companies where the skills of the workforce is crucial within a vision of competitive intelligence . This paper seeks, through a literature review, understand the structure of higher education in Brazil, describing the legal, structural and specific. It was possible to verify that the changes that occurred since the Constitution of 1988, the publication of the new Law of Guidelines and Bases of Education - LDB in 1999, the low level of public investment in higher education and market demand have opened the possibility of a greater private investment in higher education. Among private institutions, the EU has played a key role in taking responsibility instance intermediate between the knowledge produced and transmitted, meet market demand, forming qualified manpower to meet the social and economic problems relevant community.